A Comparative Fiqh Study of the provisions of Hermaphrodite between Science and Personal Status - Shammout, Hasan Taisir; Al Wardat, Abdullāh Munawar; Jabir, Tariq (Journal of Islamic and Religious Studies, 2018)
This research deals with the subject of Hermaphrodite and its provisions in the personal status, where in the first requirement of the concept of the Hermaphrodite between Islamic jurisprudence and Doctors, and found that there was a large consensus between the concept of the Hermaphrodite in the doctrine and its significance in medicine scientists, where they agreed that the collection between the reproductive tract of humankind. In the second requirement displays the search of the types of Hermaphrodite and the existence of an agreement between the Islamic Jurisprudence and the medicine scientists as a hermaphrodite two types: True hermaphroditism and Pseudo-hermaphroditism. A third requirement was to determine the gender of the Hermaphrodite where Islamic Jurisprudence adopted the external signs in determining sex, while the doctors relied on the clinical and laboratory testing, the external signs may be incompatible with the phenomenon as a result of the tests, so the reliance on virtual signs of Islamic Jurisprudence is not enough. The search then discussed issues related of personal status, where marriage is not allowed to Hermaphrodite until it becomes clear, also prevents the Khalwa. Hermaphrodite Legacy inherits the inheritance of the female and stops the rest of the heirs.